Professoras dos ciclos iniciais do ensino fundamental: a compreensão de si mesmas como educadoras matemáticas - Roberto Antonio Marques (2004)
In this work, we analyzed the understanding that teachers of the initial cycles of Elementary School have about themselves as Mathematical Educators. Semi-structured interviews with nine teachers who teach Mathematics in the initial cycles were carried out. Submitting the transcriptions to Content Analysis, we tried to define constitutive themes and arguments of that understanding. Using Discourse Analysis resources, we searched to identify and to discuss the manners, in which the interviewees structure their speeches, assume and respond (to and for) speeches and positions in the school scenery. The interviews analyse shows that the teachers understanding of themselves as Mathematical Educators grees through the mediations that are established while they search solutions for challenges of their teaching condition and practice. The concerns identified in their speeches indicate the need for approaching cultural aspects of the Mathematics teaching conditions in training courses for these teachers.